HEAVY EQUIPMENT WORKFORCE PLANNING: AN ANALYTIC HIERARCHY PROCESS FOR LOCAL WORKER COMPOSITION REGULATION COMPLIANCE â A COAL COMPANY CASE STUDY - Asmoro Nursandi, Wahyu
According to Newcastle Coal Price, the price of $457.80 in September 2022 is expected to continue to rise. This incentive encourages PT Kaltim Prima Coal to accelerate production capacity increases by adding heavy equipment and operators. Recruiting operators to support accelerated production is an operator (non-local) skill, based on Kutai East Region Regulation No 1 of 2022 (80% local worker and 20 % of non-local worker). The impact of an inappropriate operator type concerns operator supply, regional welfare levels, legal aspects and corporate image. This study aims to help management select the composition of operator types based on stakeholder expectations and regional regulations using different approaches. Problem Tree Analysis method to explore business problems. Combine ValueFocused Thinking (VFT) and Stakeholder Analysis to shape stakeholder expectations and alternative strategies. Five alternative strategies were put forward: (1) 100% skilled operator (non-local operator); (2) Combination of 80% skilled operators (non-local operators) and 20% non-skilled operators (local operators); (3) A balanced combination between skilled operators (non-local operators) and nonskilled operators (local operators); (4) Combination of 20% skilled operators (nonlocal operators) and 80% non-skilled operators (local operators); and (5) 100% nonskilled operators (local operators). The Analytic Hierarchy Process approach was analyzed using Super Decision AHP software to determine the composition of the best operator types. As a result, 100% qualified operators (non-local operators) are the best alternative. However, this alternative does not comply with legal aspect. It is therefore necessary to plan the type of operator according to the needs of the operator and negotiate with all relevant parties. The fourth option, with some adjustments to the operator composition (2024, 2027 and 2028), is the best option that can be implemented. The final step of the research is implementation planning, in which the method used is the 5W+1H method (What, When, Where, Who, When and How). After going through the described research steps, it can facilitate the interests of stakeholders: compliance with labor law aspects, reduction of unemployment index and increase of welfare index, fulfilling operator-type qualifications through a forecasting scheme. The result is that the fourth alternative with several adjustments is the best alternative.